Using an Experiential Learning Design to Teach Photography in Agricultural Communications - Lindsay W Kennedy; Cindy Akers; Rachel B Jackson (Journal of Applied Communications, 2017)
Photography is an important competency of agricultural communications graduates and is a core skill taught in the discipline’s curriculum. The [department] at [university] offers an undergraduate photography course twice yearly in two semester formats: a traditional spring semester where photography principles are taught in the classroom and a 12-day experiential intersession semester that allows for flexibility in how and where the course is taught. Both semesters utilize the same instructor, assignments, and grading rubric. While much agricultural communications research has focused on photography as a needed skill, few studies examine photography teaching methods. The purpose of this study was to compare student performance in an agricultural communications digital photography course taught with an experiential learning approach to a traditional classroom approach during the 2016 and 2017 academic calendar years. Kolb’s (1984) experiential learning theory was used as the theoretical framework for this study. Independent-samples t-tests were conducted to compare students’ cumulative mean assignment scores, individual assignment mean scores, and rubric criteria mean scores within the two instruction formats. The results suggest instruction method has an effect on student performance in agricultural communications digital photography courses. Students in the experiential intersession course had significantly higher mean cumulative assignment scores compared to students in the traditional course. While individual assignment performance was less affected by instruction format, students’ understanding of specific photography skills (rubric criteria), especially composition and clarity was higher when in the experiential intersession format.
Keywords: Photography instruction; agricultural communications; experiential learning; skill competencies